The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.1111/camh.12088
|View full text |Cite
|
Sign up to set email alerts
|

Peer Mental Health Stigmatization Scale: psychometric properties of a questionnaire for children and adolescents

Abstract: Background: The nature of stigmatizing attitudes towards children and adolescents with mental health problems has received little empirical attention, despite consensus that such attitudes are widespread. As a consequence, much less is known about stigma in childhood and adolescence and methods of stigma measurement are frequently borrowed from the adult literature. For research on this topic to develop, a theoretically based and developmentally appropriate measure is needed. This study aimed to develop a theo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
49
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(54 citation statements)
references
References 44 publications
1
49
3
Order By: Relevance
“…Unfortunately, stigmatization of YP-MHD is under-researched and not well understood (Hinshaw, 2005;McKeague et al, 2015), yet children are not necessarily stigmatized as their adult counterparts, and stigma is likely to have different long-term implications based on a child s development. This lack of a more specific understanding has resulted in expensive large scale national initiatives with predominantly disappointing results (Rickwood et al, 2004).…”
Section: The Purpose Of This Studymentioning
confidence: 99%
See 2 more Smart Citations
“…Unfortunately, stigmatization of YP-MHD is under-researched and not well understood (Hinshaw, 2005;McKeague et al, 2015), yet children are not necessarily stigmatized as their adult counterparts, and stigma is likely to have different long-term implications based on a child s development. This lack of a more specific understanding has resulted in expensive large scale national initiatives with predominantly disappointing results (Rickwood et al, 2004).…”
Section: The Purpose Of This Studymentioning
confidence: 99%
“…However, knowledge did not equate to acceptance. A number of high quality studies, predominantly comparing primary school children of 2 different ages, identified younger children to be more accepting than older children (Peterson et al, 1985;Swaim et al, 2001;Campbell et al, 2004;Bellanca and Pote, 2013;McKeague et al, 2015). This contrasted with the carefully considered work of Swords et al (2011), who found that adolescents aged 14-18 were more positive than children aged under 12, towards peers with ADHD and depression.…”
Section: Stigmatization Varies By Mental Health Diagnosismentioning
confidence: 99%
See 1 more Smart Citation
“…For mental illness, we included 30 items that were adapted from the Community Attitudes Toward the Mentally Ill (CAMI) [17] and the Community Attitude Survey to Mental Illness [18]. For children with EBD, we included 20 items that were adapted from the Attitudes About Child Mental Health Questionnaire (ACMHQ) [19] and the Peer Mental Health Stigmatization Scale (PMHSS) [20]. For people with disabilities, we included 16 items adapted from the Attitudes to Disability Scale (ADS) [21].…”
Section: Item Development and Selectionmentioning
confidence: 99%
“… 20 Recent literature emphasizes the importance of the awareness of societal stigma as conceptually distinct from personal beliefs or from self-stigma in adults as well as in children and adolescents. 21 It is important to bear in mind that perceptions of others’ beliefs are antecedents of behavior 22 and that there is evidence for the direct connection between perceived societal stigma and help-seeking. 23 …”
Section: Introductionmentioning
confidence: 99%